Ethics of archival research on political violence - Subotić, Jelena (Journal of peace research, 2021)
While archival research most often does not include direct interaction with living subjects, ethical issues surrounding this method are no less acute. These issues are even more profound in studies of violence, where the likely questions are often about life, death, murder, culpability, responsibility, punishment, or remorse. Identifying answers to such questions is a process rife with ethical minefields, including possibility of unfair affiliation of individuals with violent groups, or tendentious interpretation of past documents, or even avoidance of specific archival material if it causes direct and irreversible reputational harm. While other disciplines have begun a more thorough evaluation of the ethics of archival research, political science has so far remained largely silent on this issue. To bring these conversations to political science, I discuss three main ethical challenges in conducting archival research on political violence: the role of researcher in interpretation; harms and benefits to subjects of research; and the politics of archives and politicization of research. I illustrate the arguments with my own archival research on Holocaust remembrance in post-communist Europe. I discuss archives–public and private–as sites of my own research and present ethical challenges I encountered while working with these archival materials. I then provide a possible path toward more ethical archival research on political violence and link this path to the ongoing discussion about data and research transparency in qualitative work.